The Impact of School-Based Caries Prevention Programs on DMFT Scores and Oral Health Behaviors in School Children: School-Based Caries Prevention Programs on DMFT Scores - Memon, Shahzaman; Memon, Parveen; Maqbool, Ali; Al Absi, Mowaffaq Abdullmomen; Irfan, Naveed; Memon, Zobia Nissa; Ahsan, Shaharyar; Ejaz, Maheen (Pakistan Journal of Health Sciences, 2024)
Oral health promotion is recognized as one of the fundamental components of health-promoting schools. However, few studies have demonstrated the efficacy of supportive school environments for school children’s Oral health. This systematic review evaluates the impact of school-based caries prevention programs on DMFT scores and Oral health behaviours in school children. Objective: To evaluate the impact of school-based caries prevention programs on DMFT Scores and Oral Health Behaviors in school children. Methods: Databases like PubMed, Google Scholar, Cochrane Library, Springer, and Science Direct were searched from January 2009 to February 2024. Prisma guidelines were followed; 1, 950 studies were identified on the first search, titles, and abstracts of 500 papers were screened, 500 full-text papers were screened for eligibility, and 25 studies meeting the inclusion criteria were evaluated, relevant information was extracted, and a systematic review was conducted. Twenty-five studies were included in the systematic review. Results: These results indicate the significant role of SCPP among school-going children. Children with school-based caries prevention programs compared to those with no school-based caries prevention programs showed improved DMFT scores, reduced caries increment, healthy oral health behaviours, consistent Oral health hygienic habits, frequent use of flossing, fluoride toothpaste and mouth rinsing, and increased caries prevention knowledge. Conclusions: It was concluded that based on the pooled results, school-based caries prevention programs provide better, easily accessible, and sustainable caries prevention activities to school children to improve DMFT scores and Oral health behaviours.